Tumor Microenvironment-Induced Immunometabolic Reprogramming of Natural Killer Cells - Chambers, Andrea M.; Lupo, Kyle B.; Matosevic, Sandro (Frontiers in Immunology, 2018)
Energy metabolism is key to the promotion of tumor growth, development and metastasis. At the same time, cellular metabolism also mediates immune cell survival, proliferation and cytotoxic responses within the tumor microenvironment. The ability of natural killer cells to eradicate tumors relies on their ability to functionally persist for the duration of their anti-tumor activity. However, a tumor’s altered metabolic requirements lead to compromised functional responses of cytokine-activated natural killer cells, which result in decreased effectiveness of adoptive cell-based immunotherapies. Tumors exert these immunosuppressive effects through a number of mechanisms, a key driver of which is hypoxia. Hypoxia also fuels the generation of adenosine from the cancer-associated ectoenzymes CD39 and CD73. Adenosine’s immunosuppression manifests in decreased proliferation and impaired anti-tumor function, with adenosinergic signaling emerging as an immunometabolic checkpoint blockade target. Understanding such immunometabolic suppression is critical in directing the engineering of a new generation of natural killer cell-based immunotherapies that have the ability to more effectively target difficult-to-treat solid tumors.